THE ROLE OF PARENTAL COMMUNICATION IN SHAPING CHILDREN'S CHARACTER IN THE DIGITAL ERA - Budiono, Bagus (Jurnal Keluarga Berencana, 2024)
The rapid development of digital technology has brought both opportunities and challenges for parents in shaping their children's character. This study aims to analyze the effectiveness of parental communication strategies in shaping children's digital behavior and character development amid increasing online risks and influences. The study uses a qualitative approach with a phenomenological design to explore parents' lived experiences in communicating with their children to foster positive character development in the digital era. Purposive sampling was employed to select six parents (three mothers and three fathers) with children aged 10-15 years who actively use digital devices. Data were collected through in-depth semi-structured interviews, and a thematic analysis was used to identify key communication strategies, challenges, and parental roles in shaping digital behavior. The results showed that parents adopted various effective communication practices, specifically maintaining open dialogue through regular family discussions, implementing collaborative rule-setting, engaging in active mentoring through shared digital activities, and modeling appropriate technology use behavior. The main challenges included gaps in technological knowledge and limited quality time. Parents played roles as digital educators, supervisors, and role models. Effective communication had a positive impact on children's awareness of online risks and responsible use of technology. However, consistent implementation of rules and peer influence remain challenges. The study highlights the importance of adaptive and supportive communication practices while also addressing technological knowledge gaps and peer influences.